Electrochemical Sensor: L-Cysteine Induced Selectivity Enhancement of Electrochemically Reduced Graphene Oxide–Multiwalled Carbon Nanotubes Hybrid for Detection of Lead (Pb2+) Ions - AL-Gahouari, Theeazen; Bodkhe, Gajanan; Sayyad, Pasha; Ingle, Nikesh; Mahadik, Manasi; Shirsat, Sumedh M.; Deshmukh, Megha; Musahwar, Nadeem; Shirsat, Mehendra (Frontiers in Materials, 2020)
The selectivity improvement of Electrochemically reduced Graphene Oxide–Multiwalled Carbon Nanotubes–L-cysteine (ErGO–MWNTs–L-cys) nanocomposite modified Glassy Carbon Electrode (GCE) using drop casting method for electrochemical detection of lead (Pb2+) ions was investigated. Initially, the graphene oxide–Multiwalled Carbon Nanotubes–L-cysteine (GO–MWNTs–L-cys) nanocomposite was synthesized by a facile and cost-effective method at room temperature. The as-prepared, GO–MWNTs–L-cys exhibited good stable aqueous dispersions due to high hydrophilic nature of GO components which led to inhibiting the hydrophobicity of MWNTs. Then, the electrochemical conductivity of ErGO–MWNTs–L-cys nanocomposite modified GCE (ErGO–MWNTs–L-cys/GCE) was improved by the direct electrochemical reduction of GO–MWNTs–L-cys nanocomposite. The GO–MWNTs–L-cys nanocomposites and its individual components were characterized by Attenuated Total Reflection Infrared (ATR-IR), Raman spectroscopy, Atomic Force Microscopy and X-ray diffraction (XRD). The synergistic effect of ErGO–MWNTs–L-cys nanocomposite was confirmed by Cyclic Voltammetry (CV) measurements in [Fe(CN)6]3-/4- redox. Experimental parameters, such as pH, accumulation time and electrochemical reduction degrees, were optimized. Under optimal conditions, the electrochemical performance of modified electrodes towards Pb2+ ions was examined and it exhibited appreciable improvement at the ErGO–MWNTs–L-cys/GCE. In terms of applications, Differential Pulse Anodic Stripping Voltammetry (DPASV) was employed for the determination of Pb2+ ions on ErGO–MWNTs–L-cys/GCE. The calibration plots between anodic current and Pb2+ ions exhibited linear relationship in the range of 0.2–40 μgL-1 with the detection limit calculated to be 0.1 μgL-1 (S/N=3). Finally, the ErGO–MWNTs–L-cys/GCE showed satisfied selectivity and stable results, and the Relative Standard Deviation (RSD) was calculated to be (RSD=2.15%).